Beyond 5G: THz Spectrum Futures and Implications for Wireless Communication - Rohit Singh; Douglas Sicker (International Telecommunications Society (ITS), 2019)
There have been substantial technical and policy discussions about the spectrum needs of 5G and the necessity of expanding access to the higher frequency spectrum, including in the millimeter wave bands from 30 to 300 GHz. The focus, however, has been on bands below 60GHz, or at most 90GHz, which is the current limit of near-commercial technologies. As wireless markets continue to grow, demand may arise for spectrum in still higher frequency bands above 90GHz, including in the sub-millimeter Terahertz (THz) bands between 300GHz and 3THz. Although exploiting THz bands is at the frontiers of technical research today and the commercial case for it will depend on further demonstration of the value and constraints, it is worthwhile exploring how THz spectrum might impact wireless network architectures, business/usage cases, and spectrum policy. In this paper, we explore that challenge. We first explain some of the critical features of THz spectrum that make it both attractive and challenging to use and summarize the current state of our ability to address those challenges by reference to the current engineering research and commercialization progress on exploiting millimeter wave and higher frequencies. For example, the THz spectrum would offer virtually unbounded capacity (relative to today's demand forecasts) for supporting wide-channels and extremely high data rates, but with demanding Line of Sight (LOS) requirements. THz devices operate in very narrow beams, close to optical wavelengths, and have very limited capability to penetrate materials (e.g., even a sheet of paper is sufficient to block it). Integrating such spectrum into wireless networks will impose important requirements for antenna siting (small cell architectures) and backhaul, posing greater challenges for extending core-network services to edge-networks...
Keywords: 330; 5G; Beyond 5G; Terahertz; Wireless; Spectrum